APPLICATION OF CYCLICAL MODELS OF ORGANIZATION OF LOGISTICS TRANSPORTATION OF PRODUCTS OR RAW MATERIALS - SENYK, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The development of trade networks, the increase in the number of people in large cities, and the development of transport infrastructure require the optimization of transport and the development of new practical information and calculation technologies. Theoretical approaches to solving the problem of vehicle routing are analyzed in the paper. With the help of the approach, the company can simulate delivery for a set of customers with a periodicity of several days, which will ensure the optimization of fuel consumption and increase the enterprise's competitiveness. Based on the modern PVRP mathematical model, which is a generalization of the classic vehicle routing problem, a basic schedule is built in which suppliers and routes are combined to find the most optimal financial costs and execution of all transportation. The primary stage of the PVRP model is analyzed, at which it is necessary to present a general description of the existing situation, then describe the goal to be achieved and divide it into separate tasks. It was emphasized that an essential reason for introducing a system of minimizing losses based on a cyclic model during the transportation of milk raw materials is the minimization of its storage time because, as has already been noted more than once, this negatively affects the quality of milk. Temperature regimes and changes in microbiological indicators will determine the possible storage time of dairy raw materials. Several cyclical models of the organization of logistics transportation, which have practical experience, are considered. It is emphasized that the problem of minimizing total stocks and stocks at the plant occupies a prominent place from the point of view of prioritizing the optimization of the supply system. From a supply chain management perspective, storing materials close to the point of consumption is more efficient in reducing the risk of production line downtime. It is claimed that any model with a developed pattern is effective if the uninterrupted operation of the enterprise is ensured, minimization of total stocks, and the supplier/consumer stock ratio is at the level of 2/3. It is necessary to implement the principle of "heizunka" to ensure the efficiency of production equipment without storage losses, which will ensure the delivery of transport batches of the necessary materials of the same size and uninterrupted operation of production.
Keywords: cyclical model; supply management; logistics; routing; vehicles